Reconstructive and cosmetic surgery: the need for consumer protection / Izreen Marleeza Mansoor and Norsyazreen Mohamed Salleh - Mansoor, Izreen Marleeza; Mohamed Salleh, Norsyazreen (2008)
This research would cover the need for a specific law to govern the area of cosmetic surgery in Malaysia. The reason we embarked upon this research is because there was no research ever conducted on the matter. Therefore, our research is an attempt to consider the need of such laws to be implemented in Malaysia. Cosmetic surgery is a type of surgery that falls under plastic surgery. It is done in hopes of perfecting one's appearance. On the other hand, reconstructive surgery is a surgery conducted to reconstruct one's features. The existing laws only cover medical malpractice in a general form. This includes the Medical Act 1971, and the Private Healthcare Facilities and Services Act 1998, the law of torts and the law of contracts. The authoritative bodies that control this area of medicine is the Malaysian Medical Council (MMC), and Malaysian Association of Plastic, and Anesthetic and Craniomaxillofacial Surgeons (MAPACS). However, there are loopholes as to the existing laws. This raises the question of whether or not a specific law on cosmetic surgery is needed. Therefore, we recommend that if a specific law governing cosmetic surgery is to be enacted, it should include all aspects of cosmetic surgery, in order to fiilly-control the operations of this type of surgery.